Autofluorescence and spectral-domain optical coherence tomography of optic disk melanocytoma - Guerra,Ricardo Luz Leitão (2014)
The authors report fundus autofluorescence (FAF) and spectral-domain optical coherence tomography (OCT) findings of two consecutive patients who presented with optic disk melanocytoma (ODM). A retrospective study was performed by reviewing medical records and ophthalmic imaging examinations. Optical coherence tomography findings were sloped and brightly reflective anterior tumor surface, adjacent retinal desorganization and abrupt posterior optical shadowing. Vitreous seeds were found in one patient. Fundus autofluorescence revealed outstanding hypoautofluorescence at the tumor area and isoautofluorescence at the remaining retina. Optical coherence tomography findings of the reported cases are consistent with those reported in the reviewed literature. Fundus autofluorescence has been used in the assessment of choroidal melanocytic tumors, but not yet in melanocytomas. We assume that this is the first report of these findings and believe that when its pattern has become clearly defined, fundus autofluorescence will be a useful tool to avoid misdiagnosis in suspicious cases and for follow-up.